RECOMANDĂRILE FEDERAȚIEI EUROPENE DE PARODONTOLOGIE PENTRU PREVENIREA ÎMBOLNĂVIRILOR PARODONTALE ȘI A COMPLICAȚIILOR ACESTORA - Sorina Mihaela Solomon; Irina-Georgeta Ursărescu; Silvia Mârțu (Romanian Dental Association for Education, 2016)
The statistical global rising of the periodontal disease and of its complications represents a constant issue fought by the clinicians which determines the apparition of new protocols and guidelines emitted by the competent medical authorities. Such organisation is also the European Federation of Periodontology who, following the constant work-shops, developed a series of guidelines regarding to the management of the periodontal disease and peri-implantitis and of their complications. We propose a presentation of these guidelines with prophylactic aspect, addressed to the specialists and also to the future doctors.